Diseño del código de convivencia para el Colegio Técnico Salesiano Don Bosco - Kennedy - Aguilar Acosta, Andrea Anabel (2013)
The Coexistence’s Code delivered to The Don Bosco Technical Salesian High School, is an instrument that is going to work as moral and ethical framework to govern and regulate relationships between each member of the educational community so that they can achieved institutional objectives presents in Institutional Educational Project.